Gambaran Pelaksanaan Kepatuhan Kebersihan Tangan dalam Penanganan Pasien Gawat Darurat di Instalasi Gawat Darurat RSIA Bunda Denpasar - Putu Sundari Dewi; I Putu Arya Wijayantha; Putu Desi Yulistina (Jurnal Kesehatan Amanah, 2025)
The incidence of infection is one of the causes of death and morbidity which results in a decline in the quality of hospital services. One of the most important units in providing health services in a hospital is the Emergency Room (IGD) which provides initial or follow-up treatment for sick or injured patients that could threaten the patient's survival. The density and increase in patients in the ER is serious and can cause negative effects such as increasing the risk of contracting infections, especially in emergency patients. Based on WHO data, it was found that 61% of health workers did not comply with hand hygiene.: This type of research is descriptive observational research. Sampling in this study used non-probability sampling with total sampling technique. The research instrument used was a hand hygiene observation sheet based on the WHO hand hygiene compliance sheet with univariate data analysis. From the research results, it was found that the hand hygiene compliance rate for staff in the ER was classified as very good with hand hygiene achieved at 94%. The Emergency Department (IGD) is the front guard in providing health services to patients with emergency conditions and must continue to pay attention to patient safety principles, one of which is by implementing hand hygiene to prevent the risk of transmission of infection due to the health services provided.